Higher rate of long-term serologic response of four double doses vs. standard doses of hepatitis B vaccination in HIV-infected adults: 4-year follow-up of a randomised controlled trial - Romanee Chaiwarith (2020)
© 2019 The Author(s). Background: We previously reported that four doses or four double doses of hepatitis B vaccination regimens could not significantly increase a response rate compared with standard doses. However, the antibody levels were higher in the four doses and four double doses groups. This study followed those patients for at least 3 years and aimed to evaluate the immunogenicity of the three vaccination regimens. Methods: HIV-infected adults who had CD4+ cell counts > 200 cells/mm3, undetectable plasma HIV-1 RNA, and negative for all hepatitis B virus markers were randomly assigned to receive one of three recombinant vaccines (Hepavax-Gene® Berna, Korea) regimens: 20 μg IM at months 0, 1, and 6 (standard doses group, n = 44), 20 μg IM at months 0, 1, 2, 6 (four doses group, n = 44), or 40 μg IM at months 0, 1, 2, and 6 (four double doses group, n = 44) between February 2011 and May 4, 2012. Of 132 participants, 126 were evaluated from August 2015 to January 2016; 42 in the standard doses, 43 in the four doses, and 41 in the four double doses groups. Results: At a median duration of 49.7 months (range 46.7-53.7) after completion of the primary vaccination schedule, the percentages of responders with anti-HBs ≥ 10 mIU/mL were 57.1% (95% CI 41.5-72.8%) in the standard doses group; 76.7% (95% CI 63.6-89.9%) in the four doses group (P = 0.067 vs. the standard doses group); and 80.5% (95% CI 67.8-93.2%) in the four double doses group (P = 0.033 vs. the standard doses group). Factors associated with a responder were the vaccination schedule (either four doses or four double doses groups) and a younger age. Conclusions: Despite the highly effectiveness of the standard hepatitis B vaccination regimen at 6 months after completion, the long-term immunogenicity was lower than the four double doses regimen among HIV-infected adults with CD4+ cell counts > 200 cells/mm3 and undetectable plasma HIV-1 RNA. The standard vaccination regimen may not be the best strategy to provide long-term immune response against hepatitis B virus among HIV-infected individuals. Trial registration NCT1289106, NCT02713620